A novel molecular assay using hybridisation probes and melt curve analysis for CALR exon 9 mutation detection in myeloproliferative neoplasms. Issue 8 (31st January 2017) - Keaney, Thomas; O'Connor, Louise; Krawczyk, Janusz; Abdelrahman, Moutaz A; Hayat, Amjad H; Murray, Margaret; O'Dwyer, Michael; Percy, Melanie; Langabeer, Stehpen; Haslam, Karl; Glynn, Barry; Mullen, Ciara; et al.
Abstract : Aims: Somatic insertions/deletions in exon 9 of the calreticulin gene have been identified in patients with essential thrombocythemia and primary myelofibrosis. Over 55 mutations have been discovered, 80% of which consist of either type 1 52-bp deletion or type 2 5-bp insertion. Other mutations (types 3–5) in conjunction with types 1 and 2 account for >87% of identified mutations. The aim of this study was development of a rapid PCR-based assay using LightCycler Hybridisation Probes for the detection of type 1–5 CALR mutations. Method: A real-time PCR assay using a novel HybProbe set was developed for use on the LightCycler 480 Instrument II. The acceptor probe was labelled with LC640 and Faststart DNA Master HybProbe kit was used for PCR reactions. Results: Assay limit of detection was determined to be seven target copies with a probability of 95%. The specificity of the assay was determined by using synthetic constructs of CALR wild-type and CALR mutation types 1–5 with no non-specific detection observed. Samples from 21 patients with essential thrombocythemia (ET) and 12 patients with primary myelofibrosis (PMF), together with 29 control samples from patients diagnosed with various conditions, were screened using the assay. Of these, 24 were found to have mutations in CALR exon 9, with the assay detecting 8 type 1 mutations, 12 type 2 mutations, 2 type 24 mutations, 1 type 20 mutation and 1 31-bp deletion. Conclusions: The novel assay described has potential for application as a rapid, sensitive, high-throughput screening method in the clinical diagnostics setting.